The Use of Zakat Funds In The Economic Resilience of Natural Disaster Victims - Rahmawati Aulia Nor; Syahrani (LP2M IAIN Palopo, 2026)
The management of zakat funds by BAZNAS plays an important role in supporting the economic resilience of natural disaster victims. However, challenges such as inaccurate beneficiary identification, complex distribution procedures, and the mismatch between assistance and victims' urgent needs may reduce the effectiveness of zakat utilization. This study aims to analyze the process of beneficiary identification, the mechanism of aid distribution, and the utilization of zakat funds in strengthening the economic resilience of natural disaster victims in Hulu Sungai Utara Regency. A qualitative approach was employed using direct observation, semi-structured interviews, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing, while triangulation was applied to ensure data credibility. The findings reveal that beneficiary identification is conducted through reports from village officials and relevant agencies, followed by administrative verification and field surveys to ensure the eligibility of recipients. The distribution mechanism consists of report verification, field assessment, internal administrative procedures, and coordinated distribution involving BAZNAS, village authorities, and other stakeholders. The study also found that zakat assistance primarily focuses on fulfilling the victims' immediate basic needs, including food supplies and emergency necessities, thereby supporting their economic resilience during the early post-disaster recovery period. These findings indicate that the structured and collaborative management of zakat funds contributes to more accurate and effective disaster assistance, although future efforts should strengthen productive empowerment programs to enhance long-term economic recovery for disaster-affected communities.